Faculty and Student Perspectives on Launching a Post-Pandemic Medical School: A Philippine Case Study - Eugene John Balmores; Generaldo Maylem (International Medical Education, 2025)
The COVID-19 pandemic disrupted medical education as the shift from face-to-face to remote teaching raised concerns about learning outcomes and well-being. However, while established schools’ adaptations have been widely studied, the challenges faced by new institutions in the pandemic’s aftermath remain underexplored. This research provides a valuable case study examining the motivations and concerns of faculty and students at a newly established medical school in the Philippines during its inaugural academic year. Employing a mixed-methods design, data were obtained via validated Likert-based questionnaires assessing motivation and survey questions eliciting concerns. Descriptive and inferential approaches were utilized to analyze data. Results show that faculty motivations were primarily intrinsic, whereas students were driven by a mix of intrinsic and extrinsic factors. Subgroup analyses revealed no difference in motivational profiles across demographic characteristics. Faculty were primarily concerned with their readiness for academic roles, use of modern teaching technologies, and ensuring effective student learning. Students’ concerns focused on training quality, institutional capacity, and the uncertainties of being the pioneer batch. Despite the pioneer cohort’s small size, this study highlighted the importance of understanding faculty and student motivations and concerns, already shaped by post-pandemic realities, to provide targeted support for new medical programs in the evolving post-pandemic landscape.